Four new species of Panophrys (Anura, Megophryidae) from eastern China, with discussion on the recognition of Panophrys as a distinct genus - Lyu, Zhi-Tong; Zeng, Zhao-Chi; Wang, Jian; Liu, Zu-Yao; Huang, Ya-Qiong; Li, Wen-Zhou; Wang, Ying-Yong (Zootaxa, 2021)
The diversity of Panophrys horned toads is considered highly underestimated with a large number of undescribed cryptic species. In this work, we describe four Panophrys species from eastern China which were proposed as cryptic species by molecular data in previous study, additionally provide new information on the biogeography of these four species. Panophrys daiyunensis sp. nov. from southern Fujian, Panophrys daoji sp. nov. from eastern Zhejiang, Panophrys sanmingensis sp. nov. from the hilly area among Fujian, Jiangxi and Guangdong, and Panophrys tongboensis sp. nov. from northeastern Jiangxi, can be distinguished from all recognized congeners by a combination of morphological characteristics. The descriptions of these four new species take the recognized species of Panophrys to 51, which is the largest genus within the Asian horned toads subfamily Megophryinae. Considered as an appropriate arrangement for the Asian horned toads currently and applied in this study to describe the new species, the generic recognition of Panophrys is also discussed.